1997
DOI: 10.1038/bjc.1997.72
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visual inspection as a screening test for cervical cancer

Abstract: Summary Visual inspection of the uterine cervix by paramedical personnel has been proposed for the early detection of cervical cancer, as an alternative to routine cytology screening in developing countries. We evaluated the performance of this procedure in detecting precursor lesions and cancer in a study involving 2843 married women in Kerala, India. Two thresholds were used to define a positive test. In the lower one, any abnormality was considered as positive. The cut-off point for the high threshold was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 7 publications
1
40
0
1
Order By: Relevance
“…This result was in agreement with Suman (2013) [13] who reported positive VIA in also about two thirds of his sample. It was also in agreement with Wesley et al (1997) who reported in their study about evaluation of visual inspection as a screening test for cervical cancer that VIA test was positive in half of their sample. [15] On the other hand, this result was in disagreement with the findings of Kavita et al (2010) [11] who reported positive VIA test in less than one fifth of their study subjects and also with the findings of Ghaemmaghami et al (2004) [16] who reported in their study about "visual inspection with acetic acid as a feasible screening test for cervical neoplasia" that VIA test was positive in only less than one fifth of their study sample.…”
Section: Itemssupporting
confidence: 79%
“…This result was in agreement with Suman (2013) [13] who reported positive VIA in also about two thirds of his sample. It was also in agreement with Wesley et al (1997) who reported in their study about evaluation of visual inspection as a screening test for cervical cancer that VIA test was positive in half of their sample. [15] On the other hand, this result was in disagreement with the findings of Kavita et al (2010) [11] who reported positive VIA test in less than one fifth of their study subjects and also with the findings of Ghaemmaghami et al (2004) [16] who reported in their study about "visual inspection with acetic acid as a feasible screening test for cervical neoplasia" that VIA test was positive in only less than one fifth of their study sample.…”
Section: Itemssupporting
confidence: 79%
“…13,16 -20 The sensitivities for high-threshold downstaging to detect invasive cancer ranged from 58.3-71.4% with specificities ranging from 94.2-94.6% in previous studies. 18,19 In our study, the sensitivity to detect invasive cancer was 86.1% (31/36) and 72.2% (26/36) with low-threshold and high-threshold testing, respectively; the corresponding specificities were 75.6% and 93.6%.…”
Section: Discussionmentioning
confidence: 48%
“…Only 3 studies allowed evaluation of downstaging for different grades of dysplasia and the results of accuracy in these studies is given in Table VII. 16,18,19 However, the proportion of high-grade precursor lesions was very low in the study by Nene et al 18 The sensitivities for low-threshold downstaging to detect invasive cancer in previously reported studies varied from 50.0 -100.0%, with specificities ranging from 30.0 -59.0%. 13,16 -20 The sensitivities for high-threshold downstaging to detect invasive cancer ranged from 58.3-71.4% with specificities ranging from 94.2-94.6% in previous studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations